2018
DOI: 10.1007/s00010-018-0558-3
|View full text |Cite
|
Sign up to set email alerts
|

Spherical bodies of constant width

Abstract: The intersection L of two different non-opposite hemispheres G and H of the ddimensional unit sphere S d is called a lune. By the thickness of L we mean the distance of the centers of the (d − 1)-dimensional hemispheres bounding L. For a hemisphere G supporting a convex body C ⊂ S d we define width G (C) as the thickness of the narrowest lune or lunes of the form G ∩ H containing C. If width G (C) = w for every hemisphere G supporting C, we say that C is a body of constant width w. We present properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…Assume that ∆(R) ≥ π 2 . By Theorem 4.3 of [12], the body R is of constant width ∆(R). There is an arc pq ⊂ R of length equal to diam(R).…”
Section: Diameter Of Reduced Spherical Bodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Assume that ∆(R) ≥ π 2 . By Theorem 4.3 of [12], the body R is of constant width ∆(R). There is an arc pq ⊂ R of length equal to diam(R).…”
Section: Diameter Of Reduced Spherical Bodiesmentioning
confidence: 99%
“…Clearly, p ∈ bd(R). Take a lune L from Theorem 5.2 of [12] such that p is the center of a semicircle bounding L. Denote by s the center of the other semicircle S bounding L. By the third part of Lemma 3 in [8], we have |px| < |ps| for every x ∈ S different from s. Hence |px| ≤ |ps| for every x ∈ S. So also |pz| ≤ |ps| for every z ∈ L. In particular, |pq| ≤ |ps|. Since diam(R) = |pq| and ∆(R) = ∆(L) = |ps|, we obtain diam(R) ≤ ∆(R).…”
Section: Diameter Of Reduced Spherical Bodiesmentioning
confidence: 99%
“…Recall that bd(C • ) is the set of points r such that H(r) is a supporting hemisphere of C. Proof. In [7] there is observed that every body of constant width on S d is a body of constant diameter.…”
Section: Two Cases In Which a Spherical Convex Body Of Constant Diamementioning
confidence: 99%
“…If the spherical distance |pq| of points p, q ∈ C is δ, we call pq a diametral chord of C and we say that p, q are diametrically opposed points of C. Clearly, p, q ∈ bd(C). After Part 4 of [7] we say that a convex body D ⊂ S d of diameter δ is of constant diameter δ provided for every point p ∈ bd(D) there exists at least one point p ′ ∈ bd(D) such that |pp ′ | = δ (in other words, that pp ′ is a diametral chord of D). For the known analogous notion in E d see [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation